INFLUENCE OF PLATFORMS ON THE QUALITY OF EDUCATION IN THE ASSESSMENT OF STUDENT KNOWLEDGE IN DIGITAL EDUCATION (International journal of artificial intelligence, 2026)
This article analyzes the impact of platforms on the quality of education in assessing students' knowledge in digital education. The study analyzes the types of assessment in digital education, the possibilities of improving the quality of assessing students' knowledge through platforms and artificial intelligence, as well as the pedagogical and didactic possibilities of digital technologies, their service to increase students' knowledge, effective control of learning, and individualization of the educational process. As a result of the use of digital platforms, the effectiveness of teaching methods has increased, which will have a positive impact on the learning outcomes of students.